2020
DOI: 10.1111/jce.14688
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ventricular tachyarrhythmias and their susceptibility to antitachycardia pacing termination in patients with ischemic and nonischemic cardiomyopathy: A patient‐level meta‐analysis of three large clinical trials

Abstract: Background: Implantable cardioverter defibrillators (ICDs) reduce all-cause mortality among cardiomyopathy patients. Whether or not antitachycardia pacing (ATP) is equally effective in ischemic (ICM) and nonischemic (NICM) cardiomyopathy patients remains poorly understood. We describe the distribution of monomorphic (MVT) and non-monomorphic (polymorphic ventricular tachycardia/ventricular fibrillation [PVT/VF]) ventricular tachyarrhythmias among ICM and NICM primary prevention patients. Methods: This patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The reduced probability for patients with ischemic cardiomyopathy to receive an S-ICD might be due to fair of sustained VT in need of anti-tachycardia pacing (ATP) or incident bradyarrhythmias in need of pacing ( 17 ). However, it should be noted that only 15–20% of patients experienced a high rate of monomorphic VT during the first year after the implant with a subsequent risk is 1.8%/year; moreover, the proportions of both monomorphic VT and successful ATP was comparable between patients with ischemic and non-ischemic cardiomyopathy ( 18 ). Finally, no studies have still addressed whether the efficacy of ATP translates into hard outcomes such as mortality benefits, prevention of inappropriate shocks, and risks of pro-arrhythmias ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced probability for patients with ischemic cardiomyopathy to receive an S-ICD might be due to fair of sustained VT in need of anti-tachycardia pacing (ATP) or incident bradyarrhythmias in need of pacing ( 17 ). However, it should be noted that only 15–20% of patients experienced a high rate of monomorphic VT during the first year after the implant with a subsequent risk is 1.8%/year; moreover, the proportions of both monomorphic VT and successful ATP was comparable between patients with ischemic and non-ischemic cardiomyopathy ( 18 ). Finally, no studies have still addressed whether the efficacy of ATP translates into hard outcomes such as mortality benefits, prevention of inappropriate shocks, and risks of pro-arrhythmias ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ATP programming (number of bursts or ramps) was not specified, as well as ATP delivery for fast VTs in the VF zone, while we used multiple attempts at ATP with both bursts and ramps: this limits the comparison amongst the 3 studies. In the large meta-analysis of more than 6000 patients, Cheng et al [108] observed that ischemic and nonischemic cardiomyopathy patients have similar rates and proportions of monomorphic VT and polymorphic VT/VF episodes, ATPassociated termination of monomorphic VT being compa-rable between the two groups. As expected, in our patients ATP-terminated VAs had a significantly slower rate compared to ATP-failed VAs, though there was significant rate overlap between successfully ATP-terminated and failed episodes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ICD and left ventricular systolic dysfunction appropriate therapies due to VF are rare, accounting for less than 20% of events and affecting a minority of subjects [ 17 18 ]. Their incidence appears to be similar regardless of etiology (ischemic vs. non-ischemic [ 19 ]) and indication (primary vs. secondary prevention [ 18 ]). Only individuals with a previous history of VF appear to be more at risk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%